2018
DOI: 10.1080/17588928.2018.1504764
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and pharmacologically similar sedatives impair encoding and facilitate consolidation of both recollection and familiarity in episodic memory

Abstract: Alcohol and other pharmacologically similar sedatives (i.e., GABA positive allosteric modulators or PAMs) impair the encoding of new episodic memories but retroactively facilitate the consolidation of recently encoded memories. These effects are consistent for recollection (i.e., the retrieval of details) but some mixed results have been reported for familiarity (i.e., a feeling of knowing a stimulus was presented). Here, with dual-process models, we reanalyzed prior work testing the effects of GABA PAMs at en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 46 publications
3
24
1
Order By: Relevance
“…However, the findings from once-presented lists, indicate that normal memory functioning in the sense of semantic or gist extraction is impaired by triazolam. This is also in line with other studies reporting more global memory deficits of benzodiazepines and other GABAA positive allosteric modulators (Doss, Weafer, Ruiz, et al, 2018;Kamboj & Curran, 2006), and generally poor memory could also account for the increase in false alarms to unrelated lures that was detected with two of the tested benzodiazepines, as guessing might be increased. Triazolam also increased intrusions and false alarms in an episodic but non-false memory study (Mintzer & Griffiths, 2003b).…”
Section: Benzodiazepinessupporting
confidence: 92%
See 2 more Smart Citations
“…However, the findings from once-presented lists, indicate that normal memory functioning in the sense of semantic or gist extraction is impaired by triazolam. This is also in line with other studies reporting more global memory deficits of benzodiazepines and other GABAA positive allosteric modulators (Doss, Weafer, Ruiz, et al, 2018;Kamboj & Curran, 2006), and generally poor memory could also account for the increase in false alarms to unrelated lures that was detected with two of the tested benzodiazepines, as guessing might be increased. Triazolam also increased intrusions and false alarms in an episodic but non-false memory study (Mintzer & Griffiths, 2003b).…”
Section: Benzodiazepinessupporting
confidence: 92%
“…In particular, it appears that increased learning with repetition, which increases the rejection of false memories under placebo, is reversed under alcohol leading to a decrease in rejection of critical lures. Furthermore, in a study by Milani and Curran (2000) a low dose of alcohol (0.26-0.28 g/kg) before encoding with retrieval shortly after exerted no effect on true and false recall or recognition rates of critical lures, but increased recollective experience of false recognition responses (increased level of remember vs. know judgments; N = 20, within-subjects; however, for recent evidence that alcohol impairs both recollection and familiarity of episodic memory see Doss, Weafer, Ruiz, et al, 2018). Finally, in Mintzer and Griffiths (2001b) it was found that neither a low or a moderate alcohol dose (0.27 and 0.60 g/kg, before encoding with retrieval shortly after) affected false recognition of critical lures (N = 18, within-subjects), although the high alcohol dose did reduce true recognition and induced a more conservative response bias.…”
Section: Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with careful manipulations, such as separating encoding and retrieval phases with a ≥24-hour delay, certain drug effects can be attributed to different phases. For instance, although the amnestic effect of pre-encoding sedatives can be attributed to both encoding and consolidation, as drug effects persist after the encoding phase into consolidation, sedatives administered specifically at consolidation have the opposite effect (e.g., Doss, Weafer, Ruiz, et al, 2018). That is, administering sedatives immediately postencoding and testing memory ≥24 hours later so that drug effects do not impact memory retrieval actually enhances memory, suggesting that the impairments of pre-encoding sedatives are due to specific modulation of encoding.…”
Section: Drug Effects On Episodic Memorymentioning
confidence: 99%
“…Several studies using the remember/know procedure initially reported that sedatives administered at encoding impaired recollection but not familiarity (reviewed and reanalyzed in Doss, Weafer, Ruiz, et al, 2018). However, in a reanalysis of these data using a statistical correction for the cooccurrence of recollection and familiarity (the independence remember/know procedure; Yonelinas and Jacoby, 1995), it was found that most of these studies did in fact find sedatives to impair both recollection and familiarity.…”
Section: Sedatives (Gabaa Pams)mentioning
confidence: 99%